2012
DOI: 10.1111/j.1751-1097.2012.01093.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Donor Exisulind Is an Effective Inhibitor of Murine Photocarcinogenesis

Abstract: NO-releasing nonsteroidal anti-inflammatory drugs (NO-NSAIDs) have been shown to have anti-inflammatory, anti-proliferative and apoptosis-inducing effects in tumor cells. Here we have investigated the effects of NO-exisulind on the growth of UVB-induced skin tumor development in a murine model. We found that the topical treatment with NO-exisulind significantly reduced UVB-induced tumors in SKH-1 hairless mice. The tumors/tumor bearing mouse, the number of tumors/mouse and tumor volume/mouse decreased signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Donnini et al reported a similar inhibition of iNOS and COX-2 associated with a reduction in SCC tumor growth (27). In a previous study we also showed that COX-2 inhibitors reduce UVB-induced skin carcinogenesis (28, 29). …”
Section: Discussionmentioning
confidence: 73%
“…Donnini et al reported a similar inhibition of iNOS and COX-2 associated with a reduction in SCC tumor growth (27). In a previous study we also showed that COX-2 inhibitors reduce UVB-induced skin carcinogenesis (28, 29). …”
Section: Discussionmentioning
confidence: 73%
“…The UV irradiation unit was equipped with six Philips Ultravoilet B TL 40W/12RS lamps. Furthermore, we also used a Kodacel cellulose film (Kodacel TA401 / 407) to eliminate any UVC as described earlier (Singh et al , 2012). …”
Section: Methodsmentioning
confidence: 99%
“…In addition to UVB irradiation, group II and III mice received twice weekly topical treatments (30 min prior to UVB irradiation) with either vehicle (acetone) or NO-sulindac (5 mg/mouse dissolved in 200μl acetone) respectively. The numbers and volume (using electronic Vernier Calipers) of tumors in each animal were recorded on a weekly basis as described earlier (Singh et al , 2012). The selection of the dose of NO-sulindac is based on our previously published study related to photo-protective effects of sulindac (Athar et al , 2004).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been demonstrated that exisulind suppressed 1-methyl-1-nitrosourea (MNU)-induced mammary carcinogenesis [92], azoxymethane-induced colon carcinogenesis [93], and Nbutyl-N-(4-hydroxybutyl) nitrosamine-induced urinary bladder carcinogenesis [8] in rats, and at concentrations that were well tolerated by the animals. Exisulind also inhibited UVB-induced skin tumor development 'in vivo' by inducing apoptosis and reducing proliferation as well as epithelial-mesenchymal transition in tumor keratinocytes [94].…”
Section: Pde5 Inhibitors As Cancer Chemopreventive Agentsmentioning
confidence: 99%